2009
DOI: 10.1002/cncr.24430
|View full text |Cite
|
Sign up to set email alerts
|

Array comparative genomic hybridization identifies genetic regions associated with outcome in aggressive diffuse large B‐cell lymphomas

Abstract: BACKGROUND: Diffuse large B‐cell lymphomas (DLBCLs) are the most common type of non‐Hodgkin lymphomas. With chemotherapy and progenitor stem cell transplantation, about 60% of patients with DLBCL are long‐term survivors. The International Prognostic Index identifies patients with different outcomes. However, biologic characteristics also may help to discriminate different treatments groups. METHODS: DNA copy number changes identified by array comparative genomic hybridization (array‐CGH) were studied in 40 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 48 publications
3
22
1
1
Order By: Relevance
“…In this study, we found no significant correlation between the loss of 6p21.32 (HLA locus) and outcome. Another recurrent aberration in PCNSL was the loss of chromosome 6q (27% to 37%), which seems to occur at a higher rate than in systemic DLBCLs, where a lower frequency has been reported (32,33). We found 3 distinct minimal common deletion regions (MCRs), 6q14.1-16.3, 6q16.3, and 6q21-25.1.…”
Section: Discussionmentioning
confidence: 54%
“…In this study, we found no significant correlation between the loss of 6p21.32 (HLA locus) and outcome. Another recurrent aberration in PCNSL was the loss of chromosome 6q (27% to 37%), which seems to occur at a higher rate than in systemic DLBCLs, where a lower frequency has been reported (32,33). We found 3 distinct minimal common deletion regions (MCRs), 6q14.1-16.3, 6q16.3, and 6q21-25.1.…”
Section: Discussionmentioning
confidence: 54%
“…DCNAs are often associated with aberrant expression of oncogenes and tumor-suppressor genes, and many reports have shown that particular DCNAs are linked with poor prognosis of patients in many kinds of cancers (38,39). The association between DCNAs and outcome after surgery was analyzed by the χ 2 test, and DCNAs of 16 BAC clone regions, including gain of 11 and loss of 5 BAC clone regions, were identified as candidate prognostic markers for OSCC (p<0.01, Table IV).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in non-Hodgkin's B-cell lymphomas (NHLs) including Burkitt's lymphoma and DLBCL, recurring deletions and rearrangements of 10q23, which harbors PTEN, are observed in 5%-10% of patients (Butler et al 1999). In addition, the reduction or loss of PTEN expression is often associated with inferior survival (Abubaker et al 2007;Robledo et al 2009). These findings implicate the importance of the PTEN pathway in the progression and prognosis of specific human B-cell malignancies.…”
Section: Mir-17-92 Encodes a Mirna Polycistron That Yields Six Indivimentioning
confidence: 99%